A Review on Pharmaceutical Emulsion - Thakur, Rakesh; Sharma, Anjali; Verma, Preeti; Devi, Asha (Asian Journal of Pharmaceutical Research and Development, 2023)
The pharmaceutical term “emulsion” is most time used to indicate preparations prepared for internal use. This pharmaceutical dosage form is thermodynamically unstable and must be stabilized by the addition of emulsifying agent. Emulsified systems range from lotions having comparatively low viscosity to creams which are more viscous. There are two basic types of emulsions, that is, oil in water (O/W) and water in oil (W/O). In addition to these two types, a relatively complex emulsion, called multiple emulsions can also be formulated. Emulsions generally have certain advantages over other dosage forms as the drug solubilized may be more bioavailable. Moreover, gastrointestinal problems and first pass metabolic effect are also avoided.